Analisis Pengaruh Budaya Organisasi, Work Enggamenent (Keterlibatan Kerja), Kinerja Terhadap Quality Of Worklife (Kualitas Kehidupan Kerja) Guru, Pada Yayasan Pendidikan Karya Bahana Mandiri - Sumini; Rakhmat; Andi Muhammad Sadli (Mulia Pratama, 2023)
The quality of education is determined by the quality of teachers' work life as the main educators in schools. Some factors that affect the quality of teachers' work life include organizational culture, work engagement, and teacher performance. This study aims to determine the effect of organizational culture, work involvement, performance on the quality of work life of vocational teachers at Karya Bahana Mandiri Education Foundation. The research approach used is a quantitative approach, using measuring instruments in the form of an organizational culture scale, work engagement scale, performance scale, and quality of work life scale. The population of this study was 103 teachers of Karya Bahana Mandiri Education Foundation. From the total population the researcher took a sample of 51 respondents. Sampling was determined using the Krejcie-Mogran table. The data collection process uses a Likert scale, while data analysis uses Cronbach's Alpha with the help of the SPSS for Windows version 26 program. The results of the t test the t value of 10.954 is greater than> t table 2.010, so it can be concluded that HO is rejected and H1 is accepted, which means that partially states "There is a significant influence between X1 on Y, this can be seen from the significant value of X1, namely : 0.000 is smaller than 0.05. The significant value of X2 has a significant effect on Y, the significant value of X1 is: 0.000 is smaller than 0.05. partially states "there is a significant influence between X3 on Y and based on the Significant value, the significant value of X3 has no significant effect on Y, the significant value of X1 is : 0.818 is greater. Based on the F test results, it shows that the calculated F value of = 233.512 is greater than the F table value of 2.800. Then the calculated F value is greater than the F table value: (233.512> 2.800), so based on decision making in the f test it can be concluded that the hypothesis is accepted. Organizational Culture, Work Engagement, Performance affect the Quality of Work Life of Vocational Teachers at Karya Bahana Mandiri Education Foundation. The hypothesis proposed by the researcher can be concluded that the hypothesis simultaneously (together) affects Y (Quality of Work Life).